Zanthoxylum piperitum Benn. Attenuates Monosodium Urate-Induced Gouty Arthritis: A Network Pharmacology Investigation of Its Anti-Inflammatory Mechanisms - Sung Wook Kim; Soo Hyun Jeong; Jong Uk Kim; Mi Hye Kim; Wonwoong Lee; Cheol-Jung Lee; Tae Han Yook; Gabsik Yang (Pharmaceuticals)
Background: Monosodium urate crystal accumulation in the joints is the cause of gout, an inflammatory arthritis that is initiated by elevated serum uric acid levels. It is the most prevalent form of inflammatory arthritis, affecting millions worldwide, and requires effective treatments. The necessity for alternatives with fewer side effects is underscored by the frequent adverse effects of conventional therapies, such as urate-lowering drugs. IL-1β is a potential therapeutic target due to its significant role in the inflammatory response induced by MSU. Zanthoxylum piperitum Benn. (ZP), a shrub that possesses antibacterial, antioxidant, and anti-inflammatory properties, has demonstrated potential in the treatment of inflammatory conditions. Methods: For anti-inflammatory properties of ZP, Raw264.7 cell stimulated LPS were treated ZP and using RNA-seq with Bone marrow derived macrophage, we observed to change inflammatory gene. Pharmacological networks were conducted to select target gene associated with ZP. For in vivo, mice were injected MSU in footpad for induce gouty arthritis model. The components of ZP were analyzed using GC-MS, and distilled extracts of ZP (deZP) were prepared. Results: In vitro, deZP decreased inflammatory cytokines. However, in vivo, it also decreased paw thickness and IL-1β levels. The anti-inflammatory effects of deZP are believed to be mediated through the NLRP3 inflammasome pathway, as indicated by RNA sequencing and network pharmacology analyses. Conclusions: ZP has an anti-inflammatory effect and regulation of the NLRP3 inflammasome in vitro and in vivo. Further research, including clinical trials, is required to confirm the safety of deZP, determine the optimal dosing, and evaluate its long-term effects.